2012
DOI: 10.1111/j.1364-3703.2012.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of the miniature inverted‐repeat transposable element mimp1 in the wheat pathogen Fusarium culmorum

Abstract: High-throughput methods are needed for functional genomics analysis in Fusarium culmorum, the cause of crown and foot rot on wheat and a type B trichothecene producer. Our aim was to develop and test the efficacy of a double-component system based on the ability of the impala transposase to transactivate the miniature inverted-repeat transposable element mimp1 of Fusarium oxysporum. We report, for the first time, the application of a tagging system based on a heterologous transposon and of splinkerette-polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The lack of significant amino acid differences between the two sequences indicated an identical structure of the two proteins. When comparing the similarity of FgStuA and FcStuA to a general level of similarity between the two species, at least with partial data obtained from a transposon tagging approach [53], the level of conservation seems to be higher than average: 98.5% vs 96%. It is therefore suggested that FcStuA is under strong selective pressure having a crucial role in cell regulation and therefore being highly conserved between the two closely related species.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of significant amino acid differences between the two sequences indicated an identical structure of the two proteins. When comparing the similarity of FgStuA and FcStuA to a general level of similarity between the two species, at least with partial data obtained from a transposon tagging approach [53], the level of conservation seems to be higher than average: 98.5% vs 96%. It is therefore suggested that FcStuA is under strong selective pressure having a crucial role in cell regulation and therefore being highly conserved between the two closely related species.…”
Section: Discussionmentioning
confidence: 98%
“…The availability of genomes would facilitate targeted functional genomics studies that, at the moment, are based on the similarities of genes with F. graminearum (Baldwin et al, 2010), but this cannot explore genes that are peculiar to F. culmorum (Spanu et al, 2012).…”
Section: Functional Genomicsmentioning
confidence: 99%
“…Identification of the reinsertion site of mimp1 was achieved by Splinkerette‐PCR (Potter and Luo, ), according to the protocol described by Spanu et al . (). Flanking sequences were blast ed to the F. culmorum genome (Urban et al ., ) in order to identify mimp1 locations.…”
Section: Methodsmentioning
confidence: 97%
“…A mimp1-mediated revertant (see below) strain collection was generated from the F. culmorum FcM7 co-transformant strain, integrating a single copy of the niaD::mimp1 construct and the impalaE transposase gene under the constitutive control of the gpdA promoter (Dufresne et al, 2007;Spanu et al, 2012).…”
Section: Fungal Strains and Storage Conditionsmentioning
confidence: 99%
See 1 more Smart Citation